The Influence Of Work Motivation And Adaptation Ability On Work Productivity (Census Of Employees Of The Barecore Section Of PT. Albasi Priangan Lestari) - Lestari, Mida Septa; Yusnita, Rita Tri; Sutrisna, Arga (Universitas Dehasen Bengkulu, 2023)
This research was conducted with the aim of knowing the effect of work motivation and adaptability on the work productivity of employees of PT albasi Priangan Lestari. The method used in this study is the census method using data obtained directly through questionnaires distributed to 60 respondents who are employees of the barecore division of PT. Albasi Priangan Lestari. The technique used in this research is multiple linear regression. Based on the research results, it can be seen that work motivation and adaptability simultaneously have a significant effect on the work productivity of PT. Albasi Priangan Lestari. Partially Work Motivation has a significant effect on the work productivity of employees of PT. Albasi Priangan Lestari. Partial Adaptability has a significant effect on the work productivity of employees of PT. Albasi Priangan Lestari.